Multiplexed in vivo homology-directed repair and tumor barcoding enables parallel quantification of Kras variant oncogenicity - Ian P. Winters; Shin-Heng Chiou; Nicole K. Paulk; Christopher D. McFarland; Pranav V. Lalgudi; Rosanna K. Ma; Leszek Lisowski; Andrew J. Connolly; Dmitri A. Petrov; Mark A. Kay; Monte M. Winslow (Nature Communications, 2017)
Genome editing technologies enable the rapid interrogation of genetic alterations. Here, the authors present a CRISPR/Cas9-based platform to simultaneously investigate multiple activating point mutations in de novo cancers in mice; and generate panels of Kras-variants in different tissues to induce cancer.